Kompleksitas Hubungan Keintiman Tokoh Iryan: Perspektif Triangular Theory Of Love Dalam Novel Ar-Rajul Alladzi Āman Karya Najib Kaylani - Fadlilah, Lilik Nur; Sari Dewi, Intan; Ridwan, Muhammad Mahfud (Ukazh : Journal of Arabic Studies, 2025)
This research is motivated by the need to understand the psychological dynamics in the relationships between literary characters, particularly the aspect of emotional intimacy, which is rarely explored in depth in modern Arabic literature. The focus of this study is the novel ar-Rajul al-Laz|i> A>man by Najib Kaylani with the aim of revealing the forms of intimacy of the character Iryan through Robert J. Sternberg's Triangular Theory of Love approach, with an emphasis on the intimacy component. This research uses a qualitative method based on literature study, with the main data source being quotations in the novel that are relevant to indicators of intimacy. The results show that Iryan's intimacy is contextual: in family relationships, he expresses care, mutual understanding, and appreciation; in friendships, he shows emotional support, honest communication, and a desire to improve the well-being of loved ones; while in relationships with his partner (wife), intimacy is present in the form of intimate communication, empathy, and respect. These findings confirm that intimacy in the novel is not merely based on romantic affection, but is closely related to the values of struggle, spirituality, and ideological similarities. The implications of this study confirm that the analysis of modern Arabic literature can be enriched through the perspective of the psychology of love, thus opening up a wider interdisciplinary field of study. Furthermore, this research contributes to understanding the representation of intimacy in literary characters as a reflection of the psychological complexity of humans that is relevant to real life.